The usage of the secondary school library in Sekolah Menengah Kebangsaan Merbok, Sg. Petani / Siti Fareeza Mukhtar - Mukhtar, Siti Fareeza (Faculty of Information Management, 2011)
Nowadays some people especially students are not interested to visit the libraries. These studies to be investigating the factors that have affected students not interested in the library. This research will reveal the student user perception students of school libraries. In addition, the study will determine the level of awareness about the school libraries. Moreover, the study will also identify the resources used in the library. Finally, this study will determine the influence of manpower or expertise on the usage in the usage of the libraries among the secondary school students. The sample will be Form 1 students at Sekolah Menengah Kebangsaan Merbok, Sungai Petani because from this age, they should be informed about the use of library reference materials especially when completing their homework. The expected outcome is to improve on any weakness in the school libraries and increase the quality of services as well as improve existing facilities. Through the improvement, it can attract more students to visit the library.